2021
DOI: 10.1002/em.22464
|View full text |Cite
|
Sign up to set email alerts
|

In vitro genotoxicity of dibutyl phthalate on A549 lung cells at air–liquid interface in exposure concentrations relevant at workplaces

Abstract: The ubiquitous use of phthalates in various materials and the knowledge about their potential adverse effects is of great concern for human health. Several studies have uncovered their role in carcinogenic events and suggest various phthalate-associated adverse health effects that include pulmonary diseases. However, only limited information on pulmonary toxicity is available considering inhalation of phthalates as the route of exposure. While in vitro studies are often based on submerged exposures, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Phthalates are conservational compounds and are recognized as endocrine disruptors and peroxisome proliferators (PPs) [ 2 ]. Phthalates are involved in carcinogenesis and pulmonary disorders [ 3 ]. In vivo and epidemiological studies associated structural impairment of the lung with phthalate exposure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phthalates are conservational compounds and are recognized as endocrine disruptors and peroxisome proliferators (PPs) [ 2 ]. Phthalates are involved in carcinogenesis and pulmonary disorders [ 3 ]. In vivo and epidemiological studies associated structural impairment of the lung with phthalate exposure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In regard to concentrations, the maximum concentration tested was 300 µg/mL [ 31 ], with the majority of assessment performed in a range up to 100 µg/mL. For the plasticizers, their concentrations varied from 1–100 μM for DEHP and for MEHP [ 36 ] and 0.03–20 ng/cm 2 for DBP [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study of apoptotic markers in lung cells exposed to NPs and plasticizers verified the disturbance of the mitochondrial membrane potential [ 31 , 33 ]. It was also observed that the alteration ATP production and deregulation of the energy production mechanism [ 33 , 35 ] contributed towards cell damage [ 17 , 20 , 37 ]. Consequently, cell death has been reported [ 17 , 49 ] particularly for long exposure periods [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxicity was further tested at the chromosomal level by the micronucleus assay. Few studies have applied the micronucleus assay on advanced human lung models at the ALI; at the time of writing, we found only one publication on monocultured A549 [ 49 ], one on monocultured BEAS-2B and other bronchial cell types [ 59 ], and four studies on nasal epithelial cells from donors [ 60 , 61 , 62 , 63 ]. We successfully employed this assay to both mono- and cocultures of BEAS-2B cells exposed at the ALI.…”
Section: Discussionmentioning
confidence: 99%
“…Mitomycin-C (catalog no. A2190.0002, PanReac AppliChem [VWR/Avantor]) was used as a positive control for micronuclei induction in the micronucleus assay, with stock solution at 0.2 mg/mL in dimethyl sulfoxide (DMSO) stored at −20 °C, and exposure concentration at 0.15 µg/mL, similarly to Reference [ 49 ]. In one experiment with A549/EA.hy926 and BEAS-2B/EA.hy926 cocultures, a higher concentration (0.30 µg/mL) was additionally included.…”
Section: Methodsmentioning
confidence: 99%